Macroeconomic theory and economic policy : essays in honour of Jean-Paul Fitoussi - Fitoussi, Jean-Paul, 1942-; Velupillai, Kumaraswamy, 1947- (London ; New York : Routledge, 2004)
Jean-Paul Fitoussi needs no introduction as one of the world's foremost Macroeconomists of his generation. This celebration of his work includes contributions from Nobel Prize - winning economists Robert W. Clower and Robert Solow as well as Olivier Blanchard and leading economic theorist, Edmond Malinvaud.
Includes bibliographical references and indexes.
oif 04/02/14
Loan
Keywords: Macroeconomics; Economic policy